2022
DOI: 10.21660/2022.89.gxi361
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Reinforced Base Courses of Flexible Pavements Overlying Soft Subgrades: Insights From Large-Scale Model Experiments

Abstract: In this study, large-scale model pavement experiments (LSMPEs) were performed to assess the performance of geosynthetic-reinforced bases of flexible pavements overlying soft subgrades (with California bearing ratio equal to 1% and 5%). Two configurations of reinforcement were considered -(1) base layers reinforced with geocell (GC) alone, and (2) base layers reinforced with geocell and geogrid (GG) combinations (GC+GG). Model pavements were constructed inside the test chamber measuring 1.5m (length) × 1.5m (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, the available conventional methods such as cement or lime stabilization or fiber reinforcement consume a lot of time and money, which is why several studies have demonstrated that its use is an economic, ecological, and easy-to-construct alternative to traditional techniques. [5], [7]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the available conventional methods such as cement or lime stabilization or fiber reinforcement consume a lot of time and money, which is why several studies have demonstrated that its use is an economic, ecological, and easy-to-construct alternative to traditional techniques. [5], [7]- [11].…”
Section: Introductionmentioning
confidence: 99%